Content Analysis of Wenzi Material in Xiandai Hanyu Shang Learning as a Reference for Teaching Materials - Marsuki, Ria Riski; Pamuji, Dian Yuni; Agwinanda, Almira (Universitas Negeri Semarang, 2024)
In learning Mandarin, there are four fundamental skills that students must master: writing, reading, speaking, and listening. Writing skills are taught from the first semester to the sixth semester through courses such as 初级汉语写作上 chūjí hànyǔ xiězuò shàng (Basic Mandarin Writing I) to 高级汉语写作下 gāojí hànyǔ xiězuò xià (Advanced Mandarin Writing II), which focus on writing practice. Additionally, 汉字 hànzì material is also taught in the course 现代汉语上xiàndài hànyǔ shàng (Modern Mandarin I), but the emphasis is more on theoretical aspects. In this course, students learn about the origins and development of Hanzi characters currently in use, including the methods of character formation. The course 现代汉语上xiàndài hànyǔ shàng focuses on three main topics: 语音yǔyīn (Phonology), 文字 wénzì (Characters), and 词汇cíhuì (Vocabulary). The reference book used, 现代汉语 xiàndài hànyǔ (Modern Mandarin), is written entirely in Mandarin without translations. This is one of the reasons why the researcher aims to develop teaching materials on 汉字 hànzì (Hanzi) for the 现代汉语上 xiàndài hànyǔ shàng course, aligning them with the intended learning outcomes and the course duration. These three main topics must be covered within one semester.